Can fear of failure predict academic procrastination? A study of Indonesian university students - Nur Fauziah Karim; Minarni; Syahrul Alim (INSPIRA: Indonesian Journal of Psychological Research, 2021)
This study aims to determine the ability of fear of failure in predicting academic procrastination in students in Indonesia by involving 428 respondents (male = 52.63%). The instruments used are the academic procrastination scale and the fear of failure scale. Analysis of this research data uses a simple linear regression technique. This study showed that fear of failure affected academic procrastination significantly with a contribution value of 38.6% positive direction, while 61.4% was influenced by other factors not studied. Research confirms that students with high levels of fear of failure tend to have high levels of academic procrastination and vice versa